"MEDIOS DIGITALES, SU INFLUENCIA EN LA FORMACIÓN ACADÉMICA DE ESTUDIANTES DEL BARRIO SANTA ROSA, CANTÓN QUINSALOMA 2022” - Chiliquinga Tirado, Anthony Romario (2022)
The objective of this work is to analyze the influence of digital media in the academic training of students in the neighborhood "Santa Rosa 2" of Quinsaloma canton year 2022. To carry out this study conducted quantitative research, with the application of surveys, where the target population consisted of students of the neighborhood "Santa Rosa 2" of the canton Quinsaloma, also a literature review was conducted where variables related to the case study were addressed, through which different authors contributed to the analysis. The results show that although the students of the Santa Rosa 2 neighborhood have great accessibility to digital media, they face difficulties in understanding them, even so, they consider these media relevant in student life and in their academic training process.